Novel and Efficient One-Pot Synthesis of Spiro[Indoline-3, 4′-Pyrano [2, 3-c]pyrazole]Derivatives Catalysed by L-Proline in Aqueous Medium. (June 2013) - Yu, Jiangxia; Zhou, Yongbing; Shen, Tianhua; Mao, Wengang; Chen, Kang; Song, Qingbao
An efficient mild one-pot synthesis of spiro[indoline-3, 4′-pyrano[2, 3-c]pyrazole derivatives by a four-component reaction of hydrazine, a β-keto ester, isatin, and malononitrile catalysed by L-proline in water is reported.